حلول الموجة المنفردة لمعادلة فوم الغير الخطية في الفيزياء الرياضية (Comprehensive Journal of Science, 2025)
In the present study, two analytical approaches—the projective Riccati equation method as well as the expansion method—are employed to derive novel soliton solutions along with various exact waveforms of the nonlinear FAOM equation in fluid mechanics. The obtained solutions include bell-shaped, anti-bell, kink, anti-kink, and periodic wave profiles. A comparative analysis with previously established results is also undertaken. Furthermore, several graphical representations of the derived exact solutions have been produced with the aid of Maple software.